The Representation of Presidential Candidates of Election 2019 in Online Media in Lampung: A Reflection of Image Construction in Local Media for Presidential Election 2024 - Jejen Jaelani; Harits Setyawan; Sunarsih Sunarsih (Edukasi Lingua Sastra, 2022)
Towards the presidential election of Republic of Indonesia in 2019, many discourses related to the presidential election 2019 appeared in various mass media. The media included printed, electronic, and online news which gave information, editorial, advertisement, and other forms related to the presidential election. These various contents about the presidential election were interesting to be explored through research because they could uncover realities which were represented differently, for different purposes, and with distinctive ideology in each mass medium. These phenomena could be found not only in national online mass media, but also in online mass media in Lampung. Observing how the prospective president and vice president were represented in local online mass media was an interesting thing. That was because by using data from local online mass media, we could identify how constellation movement and political dynamics in national level were represented in local level with unique reader segments. One of provinces which were interesting to be explored through research was Lampung. As a province located in the southern area of Sumatera, Lampung was geographically strategic as the connector of Java and Sumatera. Lampung played a crucial role due to its position as the gate of Sumatera Island in logistic matters and citizen mobilization to Java and Sumatera. Based on data from Alexa (Alexa, 2019) there were five online mass media in Lampung which occupied the highest positions: saibumi.com, jejamo.com, lampost.co, radarlampung.co.id, and duajurai.co. This research aimed at describing the representation of prospective president and vice president during the presidential election 2019 in news articles published by local news sites in Lampung. It would use a discourse analysis with Corpus- Assisted Critical Discourse Analysis (CACDA). Based on data analysis, it was found that Dua Jurai, Jejamo, Saibumi, and Radar Lampung had a tendency to represent both prospective presidents and vice presidents neutrally. Meanwhile, Lampung Post had a tendency to represent the first prospective president and vice president: Jokowi-Maruf Amin in positive ways and the second prospective president and vice president: Prabowo Subianto and Sandiaga Uno in negative ways. This appeared from word-use frequency in news about both prospective presidents and vice presidents published by the mass media.